Factors Affecting Rice Quality in Kasumeeto Village, Pakue District, North Kolaka Regency - Kartomo Kartomo; Nursalam Nursalam; Helviani Helviani; Masitah Masitah; Syahrir Syahrir (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
This study was aimed to determine factors that affect the quality of paddy in Kasumeeto Village, Pakue District, North Kolaka Regency. Discriminant analysis was used as the analytical tool with a sample of 30 respondents. The results was obtained which was to determine the effect of the use of seeds, irrigation and fertilizer on the quality of lowland rice in Kusemeeto Village, Pakue District, North Kolaka Regency, can be conclude that quality of rice can be increase with increase the usage of high quality seeds and increase the usage of fertilizer. Lowland paddy is a commodity that has very promising prospects, so from the results of this study it is recommended that rice farmers should intensify the use of seeds and fertilizers because they can affect the quality of the paddy cultivated.